Bekele Desta and M. Lunga: Segmenting the Impact of Organizational Structure and Leadership on Project Resilient and Project Success in the Ethiopian Construction Industry: a FIMIX-PLS & PLS-POS Approach. International Journal of Engineering and Management Sciences. vol. 10, no. 3, pp. 73–103, doi: 10.21791/IJEMS.2025.17. - Bekele Desta, Kebede; Lunga, Msengana (International Journal of Engineering and Management Sciences, 2026)
In the original publication, the authors identified four errors.